Risk factors for healing of duodenal ulcer under antacid treatment: do ulcer patients need individual treatment?. Issue 3 (March 1988) - Massarrat, S; Müller, H G; Schmitz-Moormann, P
Abstract : In order to identify the risk factors affecting the healing of duodenal ulcer, a clinical trial with effective dose of antacid was carried out in 53 patients. Duration of ulcer history, number of relapses, duration of the last and present relapse, number, duration and severity of pain attacks in the present ulcer relapse, pain radiation to back, vomiting, appetite, smoking habit, intake of analgesics and previous haemorrhage were registered. Number of ulcers, ulcer depth, bublar narrowing, erosions, duodenitis at initial endoscopy and healing of ulcer were assessed by one endoscopist. Basic and peak acid output were measured. The extent of duodenitis on the site opposite the ulcer was determined by histological examination. Sixty per cent of the duodenal ulcers were healed after three weeks. By univariate analysis, the following factors affect the healing; pain radiation to back and pain duration during treatment (p less than 0.001), multiple or deep ulcers, narrowing of duodenal bulb (p less than 0.01), number of pain attacks and poor appetite (p less than 0.05). By the stepwise logistic regression model, the following factors were selected as predictors for healing of duodenal ulcer with 76% correct classification: pain radiation to back (p = 0.002), deep ulcer (p = 0.013), multiple ulcers (p = 0.028). Number of cigarettes/day (p less than 0.007) and male sex (p = 0.036). By this model, the prediction of healing could be accurately assessed in 78% in a new sample. Individual treatment should be carried out on the basis of these factors.